RENCANA ANGGARAN BIAYA PEMBANGUNAN PUSKESMAS 2 LANTAI KECAMATAN BOYAN TANJUNG KABUPATEN KAPUAS HULU: RENCANA ANGGARAN BIAYA PEMBANGUNAN PUSKESMAS 2 LANTAI KECAMATAN BOYAN TANJUNG KABUPATEN KAPUAS HULU - Sumarni, Sumarni Sumarni; Karlina, Heni; Arianti, Iin; Rianti, Rika (RETENSI, 2024)
ABSTRACT The construction of a 2-story health center in Boyan Tanjung District, Kapuas Hulu Regency is a strategy implemented in managing the process of building health facilities. This journal involves project management for the construction of a 2-story health center in Boyan Tanjung District. When planning construction management this project will produce work volume calculations, cost budget plans (RAB), bar charts, S curves, labor requirements tables, identification of potential hazards, personal protective equipment determination tables. As well as using appropriate and effective construction methods to encourage successful implementation. Judging from the methods used, namely secondary data in the form of work drawings, analysis of unit prices for work according to government regulations and housing prices, wages and materials according to mayoral regulations, and literature in the form of books and journals. The results of the planning method above, obtained a budget plan of Rp. 5,561,427,000.00, project work time plan for 14 weeks based on the S curve or ±98 calendar days, contains quality specifications and how to carry out each job as well as the tools and materials used, the maximum workforce required is 33 people, identification of potential hazards shows the level value severity and frequency of work accidents and requires a work safety plan cost of Rp. 45,968,250.00. Keywords: planning, management, project, construction, effectiv